Plant-mediated silver nanoparticles: antibacterial activity and their influence on plant growth characteristics - Ahmad, Siti Aqlima; Veerasingam, Pavithran; Mohd Sanusi, Ruzana Adibah; Mohamad Azzeme, Azzreena; Shaharuddin, Noor Azmi; Sawalha, Hanadi; Darham, Syazani; Abiri, Rambod (Malaysian Society for Biochemistry and Molecular Biology, 2024)
Metal nanoparticles (MNPs) have a range of appealing physical and chemical properties to produce antimicrobial agents. The growing demand for green MNPs has received significant research attention to developing efficient, quick, affordable, and environmentally sustainable methods of MNPs synthesis. Silver nanoparticles (AgNPs) are among the most frequently investigated noble MNPs known for their potential in antimicrobial applications. The plant extracts as reducing and capping agents to obtain AgNPs and are favoured due to their efficient and non-hazardous activity. A wide range of AgNPs bioactivities has shown their capability to combat different microbial resistance issues. Plant-mediated AgNPs are an easy and sustainable method to produce noble antimicrobial NPs. On the other hand, these NPs have positively or negatively impacted the plant growth parameters. In this review, we highlight the plant-mediated synthesis of AgNPs, their potential in antimicrobial activity for various fields and their influence on plant growth parameters.